Method for regenerating damaged oxide solid electrolyte through electric heating pulse
The Joule heat generated by the Joule heat base is powered on and repaired in segments. The problem that the oxide solid electrolyte is susceptible to lithium dendrites is solved, and efficient repair and quality improvement is achieved, extending the service life of the electrolyte and reducing costs.
Patent Information
- Application Number
- CN202411849902.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The solid oxide electrolyte is susceptible to short circuits caused by the growth of lithium dendrites, resulting in structural damage and performance degradation. Frequent replacement increases the cost of use. In addition, the damaged electrolyte contains rare earths and rare elements with high recycling value, and existing regeneration methods are difficult to effectively recover and repair.
The Joule heat substrate is powered on to generate Joule heat, and the damaged oxide solid electrolyte is sintered and repaired in stages. By regulating the heating rate and temperature, impurities are removed and densification is promoted, which significantly shortens the regeneration time and improves efficiency.
Repair and regeneration are completed in a very short time, effectively reducing the volatility of lithium ions, improving the quality and performance of regenerated electrolytes, extending the duration of use, increasing the number of cycles, and reducing application costs.
Smart Images

Figure CN119683592A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery material resource recycling, and relates to a method for regenerating damaged oxide solid electrolyte by electric thermal pulse. Background Art
[0002] Solid electrolytes can be divided into three types according to the type of electrolyte: oxides, sulfides, and polymers. Oxide solid electrolytes have higher lithium ion conductivity (10 -3 -10 -4 S / cm), high mechanical strength, low interfacial resistance and good chemical stability, making it a strong candidate for the next generation of electrolyte materials. However, oxide solid electrolytes are susceptible to short-circuit phenomena caused by the growth of lithium dendrites, which leads to structural damage, performance degradation, and ultimately failure of the oxide solid electrolyte. New oxide solid electrolytes must be replaced. Frequent replacement of oxide solid electrolytes leads to increased use costs, which is not conducive to the practical application of oxide solid electrolytes. At the same time, damaged oxide solid electrolytes often contain some rare earth elements (such as lanthanum and hafnium) and rare elements (such as zirconium, tantalum, niobium, scandium, etc.), which have high recovery values. In the regeneration process of oxide solid electrolytes, these elements can also be recovered to achieve resource recycling and reuse. Therefore, it is of great significance to regenerate damaged oxide solid electrolytes.
[0003] The quality of the oxide solid electrolyte after regeneration directly affects its duration and number of cycles. The better the quality of the oxide solid electrolyte after regeneration, the longer its number and duration of cycles, which is more conducive to its practical application.
[0004] Therefore, it is necessary to provide a method for electrothermal pulse regeneration of damaged oxide solid electrolytes to improve the regeneration quality of damaged oxide solid electrolytes, thereby making more effective use of the oxide solid electrolytes. Summary of the invention
[0005] In order to solve the problems in the background technology, the present invention adopts Joule heat to generate Joule heat by energizing a Joule heat substrate to sinter and repair the damaged oxide solid electrolyte, thereby greatly shortening the time required for regeneration of the damaged oxide solid electrolyte, improving the regeneration efficiency, quickly removing impurities, and significantly reducing the volatilization of lithium ions, thereby effectively weakening the quality degradation caused by the regeneration process of the oxide solid electrolyte, and obtaining a regenerated oxide solid electrolyte with higher quality.
[0006] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0007] The method specifically comprises: placing a damaged oxide solid electrolyte between Joule heat substrates, applying electricity to the Joule heat substrates, and the Joule heat substrates generate Joule heat to sinter the damaged oxide solid electrolyte in sections, and after the sintering is completed, a regenerated oxide solid electrolyte is obtained.
[0008] Preferably, the staged sintering is divided into two stages, and the heating rate of the first stage is 10-10 5 ℃ / s, sintering temperature is 300-800℃, constant temperature time is 5-600s; the second stage sintering heating rate is 10 2 -10 5 ℃ / s, sintering temperature is 900-2000℃, and constant temperature time is 1-300s.
[0009] Preferably, the segmented sintering is carried out in an atmosphere of air, oxygen, argon or in a vacuum environment.
[0010] Preferably, during the sintering process, a pressure of 0-10T is applied to the damaged oxide solid electrolyte.
[0011] Preferably, the Joule heat substrate is one of a carbon substrate, a molybdenum substrate and a tungsten substrate.
[0012] Preferably, the carbon substrate comprises one of carbon cloth, carbon felt and carbon fiber; the molybdenum substrate is a molybdenum sheet; and the tungsten substrate is a tungsten sheet.
[0013] Preferably, the oxide solid electrolyte is one of a NASICON-type oxide solid electrolyte, a garnet-type oxide solid electrolyte, and a perovskite-type oxide solid electrolyte.
[0014] Preferably, the chemical formula of the NASICON type oxide solid electrolyte is Li 1+x Al x Z 2-x (PO4)3, wherein Z is one or more of Ti, Ge, and Zr, x is the atomic number, 0≤x≤3; the chemical formula of the garnet-type oxide solid electrolyte is Li 7-x Ln3Z 2-x A x O 12 , wherein A is one or more of Ta, Nb, Sn, Hf, Sc, Ge, 0≤x≤0.75; the chemical formula of the perovskite oxide solid electrolyte is Li 3x La 0.66-x TiO3, of which 0 <x≤0.16。
[0015] Preferably, the damaged oxide solid electrolyte has a diameter of 5-50 mm and a thickness of 0.5-10 mm.
[0016] Beneficial effects of the present invention:
[0017] 1. The present invention uses Joule heat to generate Joule heat by electrifying the Joule heat substrate to sinter and repair the damaged oxide solid electrolyte. The time of the entire repair and regeneration process can be controlled within 10 minutes, and the repair and regeneration efficiency of the damaged oxide solid electrolyte is extremely high.
[0018] 2. Lithium ions are essential components in oxide solid electrolytes. The lithium ion content in oxide solid electrolytes directly affects their performance. During the repair and regeneration process, the damaged oxide solid electrolyte needs to be heated to a higher temperature. Lithium ions will volatilize when heated. The longer the heating time, the more lithium ions will volatilize, and the more the quality of the regenerated oxide solid electrolyte will decrease. The present invention can complete the entire repair and regeneration process in a very short time, and can effectively reduce the volatilization of lithium ions, thereby improving the quality of the regenerated oxide solid electrolyte.
[0019] 3. The present invention removes volatile impurities such as organic matter on the surface of the damaged oxide electrolyte through the first stage of sintering, and promotes the densification of the damaged oxide solid electrolyte through the second stage of sintering, and finally obtains an oxide solid electrolyte with uniform grain size, complete structure, high conductivity and mechanical strength, so that it has high stability and cycle performance in practical applications.
[0020] 4. The oxide solid electrolyte repaired and regenerated by the method of the present invention has a higher quality, can effectively extend its service life, and can increase the number of times the oxide solid electrolyte is repaired and regenerated, thereby improving the utilization rate of the oxide solid electrolyte and reducing the application cost of the oxide solid electrolyte.
[0021] 5. The method of the present invention is simple, easy to operate, the process is easy to control, the overall repair and regeneration cost is low, and it is suitable for industrial promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Entities of the oxide solid electrolyte in the original state, damaged state and after regeneration in Example 1 of the present invention, wherein (a) is an entity diagram of the original state, (b) is an entity diagram of the damaged state, and (c) is an entity diagram of the regenerated state;
[0023] Figure 2 The figures are scanning electron microscope (SEM) images of the oxide solid electrolyte in the damaged state and after regeneration in Example 1 of the present invention, wherein (a) is the SEM image of the damaged state, (b) is the SEM image after regeneration, (c) is a partial enlarged image of (a), and (d) is a partial enlarged image of (b);
[0024] Figure 31 is an X-ray diffraction (XRD) diagram of the oxide solid electrolyte in a damaged state and after regeneration in Example 1 of the present invention;
[0025] Figure 4 The room temperature impedance spectroscopy (EIS) diagram of the oxide solid electrolyte in the original state and after regeneration in Example 1 of the present invention;
[0026] Figure 5 The figures are scanning electron microscope (SEM) images of the oxygen solid electrolyte in the damaged state and after regeneration in Example 3 of the present invention, wherein (a) is the SEM image of the damaged state, and (b) is the SEM image after regeneration;
[0027] Figure 6 is an X-ray diffraction (XRD) diagram of the oxide solid electrolyte after regeneration in Comparative Example 1 of the present invention;
[0028] Figure 7 This is a scanning electron microscope (SEM) image of the oxide solid electrolyte after regeneration in Comparative Example 1 of the present invention;
[0029] Figure 8 This is a room temperature impedance spectroscopy (EIS) graph of the oxide solid electrolyte after regeneration in Comparative Example 1 of the present invention.
[0030] Fig. 9 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with specific embodiments.
[0032] Example 1
[0033] In this embodiment, the damaged oxide solid electrolyte is repaired and regenerated by the following method:
[0034] The damaged lithium aluminum titanium phosphorus oxide solid electrolyte Li 1.4 Al 0.4 Ti 1.6 (PO4)3(LATP) was placed at the center between two rectangular carbon felts of the same size, so that LATP was completely wrapped by the carbon felt, and a pressure of 5T was applied to LATP. In an air atmosphere, the carbon felt was energized to generate Joule heat under the action of the current, and the damaged LATP electrolyte was sintered in stages by hot pressing. By adjusting the current, the carbon felt was heated to 300℃ at a heating rate of 10℃ / s to perform the first stage sintering of LATP. After keeping the temperature for 600s, the current was adjusted again to heat the carbon felt at a heating rate of 10℃ / s. 2 The temperature was raised to 900°C at a heating rate of ℃ / s for the second sintering of LATP, with a holding time of 300s. After sintering, regenerated LATP sheets were obtained.
[0035] Take a picture of the regenerated LATP sheet, such as Figure 1 As shown in (c), SEM experiments were performed on the regenerated LATP, and the results are shown in Figure 2 As shown, the XRD experiment was carried out on the regenerated LATP sheet, and the results are shown in Figure 3 As shown, the room temperature impedance of the regenerated LATP sheet was tested, and the results are as follows Figure 4 shown.
[0036] pass Figure 1 By comparing (a, b, c), it can be seen that the surfaces of the original LATP sheet and the regenerated LATP sheet are both in a clean state, while black spots appear on the surface of the damaged LATP sheet, which are organic impurities, lithium dendrites and their derivatives generated during the use of LATP. This shows that after the repair and regeneration method of the present invention, the organic matter on the LATP surface is volatilized, and at the same time, the lithium dendrites and their derivatives in the grain boundaries react in situ as sintering aids, so that the regenerated LATP sheet has no black spots. The lithium dendrites and their derivatives in the grain boundaries can serve as sintering aids to effectively fill the voids and microcracks in the oxide solid electrolyte, make the electrolyte grain size more uniform, and improve the structural integrity of the electrolyte, thereby improving the ionic conductivity and mechanical strength of the electrolyte, and enhancing its use stability and cycle performance.
[0037] pass Figure 2 From the comparison between (b) and (c), it can be seen that after the damaged LATP sheet is repaired and regenerated, its black patch material (organic impurities, lithium dendrites and their derivatives) is assimilated by the surrounding LATP grains and regenerated into uniform and dense grains.
[0038] pass Figure 3 It can be seen that the XRD spectrum of the regenerated LATP sheet completely corresponds to the LATP standard PDF spectrum, indicating that the repair and regeneration method of the present invention will not change the crystal structure of the oxide solid electrolyte, so that after repair and regeneration by the method of the present invention, the oxide solid electrolyte can be used normally.
[0039] Combination Figure 4 The room temperature ionic conductivity of the original LATP sheet was obtained by fitting and calculating the impedance data to be 1.08×10 -4 S / cm, and the room temperature ionic conductivity of the regenerated LATP sheet is 3.19×10 -4S / cm, the room temperature ionic conductivity of the regenerated LATP sheet has been significantly improved. On the one hand, it shows that the method of the present invention avoids the volatilization of lithium during the repair and regeneration process due to the extremely short time, and will not affect the quality of the oxide solid electrolyte. On the other hand, it proves that lithium dendrites and their derivatives can be used as sintering aids in the repair and regeneration process to react in situ, thereby increasing the lithium ion concentration in LATP while eliminating lithium dendrites and their derivatives, so that the ionic conductivity of the regenerated LATP sheet is increased. It also proves that the regenerated oxide solid electrolyte obtained by the method of the present invention has a higher quality. Compared with the original LATP, the improvement of the ionic conductivity of the LATP sheet after repair and regeneration is mainly due to the fact that LATP will introduce lithium that cannot conduct electricity due to the formation of lithium dendrites and their derivatives during normal use. Although these lithium dendrites and their derivatives increase the amount of lithium, they cannot provide effective ion conduction, but will cause structural damage to the oxide solid electrolyte, resulting in a decrease in electrolyte performance. After the damaged oxide solid electrolyte is repaired and regenerated by the method of the present invention, not only can these useless lithium dendrites and their derivatives be removed or converted, thereby restoring the ion conduction channel, but the concentration of available lithium ions in LATP can also be increased, ultimately making the ionic conductivity of the repaired and regenerated oxide solid electrolyte better than that of the original electrolyte.
[0040] Example 2
[0041] In this embodiment, the damaged oxide solid electrolyte is repaired and regenerated by the following method:
[0042] The damaged lithium aluminum titanium phosphorus oxide solid electrolyte Li 1.4 Al 0.4 Ti 1.6 (PO4)3(LATP) was placed at the center between two rectangular molybdenum sheets of the same size, so that LATP was completely wrapped by the molybdenum sheets. No pressure was applied to LATP. In an argon atmosphere, the molybdenum sheets were energized to generate Joule heat under the action of the current. The damaged LATP electrolyte was sintered in sections by hot pressing. By adjusting the current size, the molybdenum sheets were sintered at a speed of 10 3 The temperature was raised to 600℃ at a heating rate of 10℃ / s to carry out the first stage sintering of LATP. After keeping the temperature for 20s, the current was adjusted again to make the carbon felt heat up at a rate of 10℃ / s. 4 The temperature was raised to 1000°C at a heating rate of ℃ / s for the second sintering of LATP, with a holding time of 5s. After sintering, regenerated LATP sheets were obtained.
[0043] The performance of the regenerated LATP sheet obtained in this example is similar to that of the regenerated LATP sheet in Example 1.
[0044] Example 3
[0045] In this embodiment, the damaged oxide solid electrolyte is repaired and regenerated by the following method:
[0046] The damaged lithium lanthanum zirconium tantalum oxide solid electrolyte Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 The LLZTO was placed at the center between two rectangular tungsten sheets of the same size, so that the LLZTO was completely wrapped by the tungsten sheets. A pressure of 10T was applied to the LLZTO. 3 Under vacuum conditions of 10 Pa, the tungsten sheet was electrified to generate Joule heat under the action of the current, and the damaged LLZTO electrolyte was sintered by hot pressing. By adjusting the current size, the molybdenum sheet was sintered at a speed of 10 5 The temperature was raised to 800℃ at a heating rate of 10℃ / s to carry out the first stage sintering of LLZTO. After keeping the temperature for 5s, the current was adjusted again to make the carbon felt heat up at a rate of 10℃ / s. 5 The temperature was raised to 2000°C at a heating rate of ℃ / s for the second sintering of LLZTO, with a holding time of 1s, and a regenerated LLZTO sheet was obtained after sintering.
[0047] The SEM experiment was carried out on the regenerated LLZTO sheet, and the results are as follows Figure 5 (b) as shown.
[0048] pass Figure 5 (a) It can be seen that bubble-shaped lithium dendrites and their oxidized substances appear in the damaged LLZTO sheet. After repair and regeneration by the method of the present invention, the bubbles in the LLZTO sheet are assimilated by the surrounding LLZTO grains and regenerated into uniform and dense cubic new LLZTO grains (such as Figure 5 (as shown in (b)).
[0049] Comparative Example
[0050] In this comparative example, a muffle furnace is used to sinter the damaged LATP. The damaged LATP used in this comparative example is the same as that in Example 1. The specific sintering process of this comparative example is: the damaged LATP is placed in the muffle furnace, and the heating rate is set to 3°C / min. After the temperature of the muffle furnace is increased to 900°C, it is kept warm for 5 hours, and then the LATP is cooled to room temperature with the furnace to obtain a regenerated LATP sheet.
[0051] The XRD test was carried out on the regenerated LATP sheet of this comparative example, and the results are as follows: Figure 6 As shown, the regenerated LATP sheet was subjected to SEM experiment, and the results are shown in Figure 7 As shown, the room temperature impedance of the regenerated LATP sheet was tested, and the results are as follows Figure 8 shown.
[0052] pass Figure 6It can be seen that when the XRD result diagram of the LATP sheet in this comparative example is compared with the standard card, TiO2 and Li3PO4 impurities are generated.
[0053] pass Figure 7 It can be seen that the regenerated LATP sheet in this comparative example has many pores and cracks and poor density, which indicates that the quality of the regenerated LATP sheet in this comparative example is poor.
[0054] Combination Figure 8 After fitting and calculation, the room temperature ionic conductivity of the regenerated LATP sheet in this comparative example is 4.38×10 -5 S / cm, and its room temperature ionic conductivity is much lower than that of the original LATP, which proves again that the quality of the regenerated LATP sheet in this comparative example is poor.
[0055] In summary, the method of the present invention can efficiently repair damaged oxide solid electrolytes, and effectively improve the quality of the repaired and regenerated oxide solid electrolytes, so that the oxide solid electrolytes can be used continuously for a long time, and also increase the number of repair and regeneration times of the oxide solid electrolytes, laying an excellent foundation for the practical application of oxide solid electrolytes.
[0056] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.
Claims
1. A method for regenerating a damaged oxide solid electrolyte by electrothermal pulse, characterized in that: The method specifically comprises: placing a damaged oxide solid electrolyte between Joule heat substrates, applying electricity to the Joule heat substrates, and the Joule heat substrates generate Joule heat to sinter the damaged oxide solid electrolyte in sections, and after the sintering is completed, a regenerated oxide solid electrolyte is obtained.
2. The method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to claim 1, characterized in that: The staged sintering is divided into two stages. The heating rate of the first stage is 10-10 5 ℃ / s, sintering temperature is 300-800℃, constant temperature time is 5-600s; the second stage sintering heating rate is 10 2 -10 5 ℃ / s, sintering temperature is 900-2000℃, and constant temperature time is 1-300s.
3. The method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to claim 1, characterized in that: The segmented sintering is performed in an atmosphere of air, oxygen, argon or in a vacuum environment.
4. The method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to claim 1, characterized in that: During the sintering process, a pressure of 0-10T is applied to the damaged oxide solid electrolyte.
5. A method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to any one of claims 1 to 4, characterized in that: The Joule heat substrate is one of a carbon substrate, a molybdenum substrate and a tungsten substrate.
6. The method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to claim 5, characterized in that: The carbon substrate includes one of carbon cloth, carbon felt and carbon fiber; the molybdenum substrate is a molybdenum sheet; and the tungsten substrate is a tungsten sheet.
7. A method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to any one of claims 1 to 4, characterized in that: The oxide solid electrolyte is one of a NASICON-type oxide solid electrolyte, a garnet-type oxide solid electrolyte, and a perovskite-type oxide solid electrolyte.
8. The method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to claim 7, characterized in that: The chemical formula of the NASICON type oxide solid electrolyte is Li 1+x Al x Z 2-x (PO4)3, wherein Z is one or more of Ti, Ge, and Zr, x is the atomic number, 0≤x≤3; the chemical formula of the garnet-type oxide solid electrolyte is Li 7-x LqCy 2-x A x O 12 , wherein A is one or more of Ta, Nb, Sn, Hf, Sc, Ge, 0≤x≤0.75; the chemical formula of the perovskite oxide solid electrolyte is Li 3x La 0.66-x TiO3, of which 0 <x≤0.16。 9. A method for regenerating damaged oxide solid electrolyte by electrothermal pulse according to any one of claims 1 to 4, characterized in that: The damaged oxide solid electrolyte has a diameter of 5-50 mm and a thickness of 0.5-10 mm.
Citation Information
Patent Citations
Recycling method for oxide-based solid electrolyte with original phase, method of fabricating lithium battery and green battery thereof
CN112713326A
Direct recovery and regeneration method of oxide solid electrolyte
CN115441080A
Recycling method of garnet type oxide solid electrolyte invalid mother powder
CN118281356A
Rapid densification preparation method of oxide solid electrolyte of lithium ion battery
CN118724582A
In-operando electrochemical dendrite healing in lithium-ion battery cells
US20230108561A1
